Flexibility evaluation of psammophytes using Young’s modulus based on 3D numerical simulation - Xiang, Hongxu; Wu, Xiaoxu; Wang, Rende; Shi, Chunming; Fang, Hui; Zou, Xueyong; Guo, Zhiyi; Yin, Jie; Liu, Xingchen; Yang, Xiaofan (Frontiers in Environmental Science, 2024)
Flexible psammophytes play an important role in controlling soil wind erosion and desertification, owing to their characteristics. Although flexibility of psammophytes has been considered in previous studies, the interaction between flexible psammophytes and the surrounding airflow field still remained unclear. In this study, we used the Young’s modulus to describe plant flexibility and conducted a 3D computational fluid dynamics simulation using a standard k-ε model and a fluid–structure interaction model. Taking Caragana korshinskii (Caragana), a typical psammophyte, as the research object, we constructed 3D geometric models with different diameters to simulate the airflow field around the flexible psammophytes. By comparing with the simulation results of rigid plants and simulation results of flexible plants at different wind speeds, we could verify the rationality of the simulation method. Based on the simulation results, the maximum swing amplitude of the model and the Young’s modulus were found to have a negative correlation, presenting an exponential functional relationship with good fitting. The relationship between the actual Young’s modulus of the plant branches and that of different diameter models in the numerical simulation was also established. This study is expected to improve our basic understanding of the interaction between flexible psammophytes and the surrounding airflow field, and provide some qualitative reference for the numerical simulation of the airflow field around flexible psammophytes.